English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-03-18 05:28:39 · 4 answers · asked by Dave 4 in Science & Mathematics Mathematics

4 answers

f(-1)=-5(-1)-1=5-1=4

2007-03-18 05:32:51 · answer #1 · answered by Anonymous · 0 1

This means to plug -1 into your equation
-5(-1) -1
5-1= 4

2007-03-18 12:34:12 · answer #2 · answered by ignoramus 7 · 0 1

just substitute x=-1

-5(-1)-1=5-1=4

2007-03-18 12:31:37 · answer #3 · answered by more1708_par 2 · 0 0

=-5 X -1 -1
=5-1
= 4
f(-1)=4

2007-03-18 12:54:54 · answer #4 · answered by Sarah Koshy 2 · 0 1

fedest.com, questions and answers